The effect of rest periods on energy system contribution during interval swimming - Shimoyama, Y.; Tomikawa, M.; Nomura, T. (European Journal of Sport Science, 2003)
The purpose of this study was to investigate the effect of rest periods on energy system contribution during interval swimming and whether the energy system contribution varied depending on the swimmer's specialty, such as swimmers who specialize in the 100 m or 200 m. Seven highly-trained male varsity swimmers performed three different tests: a 10-min continuous test (CON), 10 × 1-min interval test with rest periods of 20 s (INT20) and 10 × 1-min interval test with rest periods of 30 s (INT30). Swimming velocity during all tests was set to maintain a blood lactate of 4 mM determined by progressive swimming. The relative aerobic and anaerobic energy system contribution was evaluated from accumulated oxygen uptake and oxygen deficit. Aerobic energy system contribution in CON, INT20, and INT30 was 93.3 ±1.1, 81.0 ±10.4, and 67.4 ±8.5%, and anaerobic contribution was 6.7 ±1.1, 19.0 ±10.4, and 32.6 ±8.5%, respectively. There were significant differences.